2014
DOI: 10.1097/ftd.0b013e31829da6dd
|View full text |Cite
|
Sign up to set email alerts
|

Impact of POR*28 on the Pharmacokinetics of Tacrolimus and Cyclosporine A in Renal Transplant Patients

Abstract: Our results show that the POR*28 allele is associated with increased in vivo CYP3A5 activity for Tac in CYP3A5 expressers, whereas POR*28 homozygosity was associated with a significant higher CYP3A4 activity in CYP3A5 nonexpressers for both Tac and CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 35 publications
7
67
0
3
Order By: Relevance
“…[45] In a study in 71 healthy Chinese volunteers, Zhang et al [46] demonstrated that CYP3A5 expressers carrying the POR*28 variant allele had a Tac exposure that was about 40% lower than CYP3A5 expressers with wildtype POR. The increased Tac dose requirement of CYP3A5-expressing kidney transplant recipients carrying the POR*28 (T) variant allele was recently confirmed by Elens and Lunde et al [47,48] Taken together, these studies suggest that the POR*28 SNP leads to increased CYP3A5-mediated Tac metabolism, possibly resulting from a facilitated interaction between POR, CYP3A5, and Tac. In CYP3A5 non-expressers, Tac metabolism depends entirely on CYP3A4 and POR*28 apparently does not influence CYP3A4 activity to a clinically relevant degree.…”
Section: Porsupporting
confidence: 52%
“…[45] In a study in 71 healthy Chinese volunteers, Zhang et al [46] demonstrated that CYP3A5 expressers carrying the POR*28 variant allele had a Tac exposure that was about 40% lower than CYP3A5 expressers with wildtype POR. The increased Tac dose requirement of CYP3A5-expressing kidney transplant recipients carrying the POR*28 (T) variant allele was recently confirmed by Elens and Lunde et al [47,48] Taken together, these studies suggest that the POR*28 SNP leads to increased CYP3A5-mediated Tac metabolism, possibly resulting from a facilitated interaction between POR, CYP3A5, and Tac. In CYP3A5 non-expressers, Tac metabolism depends entirely on CYP3A4 and POR*28 apparently does not influence CYP3A4 activity to a clinically relevant degree.…”
Section: Porsupporting
confidence: 52%
“…However, the strength of this association seems weak, 19,23 and the impact of POR*28 on Tac doses requirements is limited (15%-20%), compared with those mediated by CYP3A5 and CYP3A4 variants. 21,23 Whether POR genotyping should be integrated in routine pharmacogenetic screening before Tac introduction in solid organ transplantation is not established, and the definite proof on the clinical impact of this polymorphism remains to be validated by independent large-scale studies.…”
Section: Introductionmentioning
confidence: 99%
“…123 Studies in renal transplant patients showed that the presence of SNPs in CYP3A4 and CYP3A5 influences blood levels of CsA. 124 Pharmacoge-netic testing of SNPs in CYP3A4 and CYP3A5 may also be of use in the treatment of patients with CsA and needs further investigation.…”
Section: -119mentioning
confidence: 99%